Pelatihan Pembuatan Bahan Ajar bagi Guru PPKn MTs di Kabupaten Ponorogo - Ambiro Puji Asmaroini; Ardhana Januar Mahardhani (J-ABDIPAMAS (Jurnal Pengabdian Kepada Masyarakat), 2019)
Todays, PPKn teachers in MTs in Ponorogo district need information and guidance to be able to make modules as teaching materials. The module is useful for teaching and learning activities in class. The purpose of this activity is that PPKn teachers in MTs in Kabupaten Ponorogo are able to: 1) Understand the material about modules, 2) Understand the procedures for preparing modules, and 3) Arrange / Make PPKn modules for SMP / MTs. this activity uses training methods and practice in making modules, lectures and frequently asked questions. From 13 participants producing PPKn modules for SMP / MTs grade 7 and 8. 12 participants were able to complete 1 chapter module, while 1 other participant was able to complete 1 module for grade 8 SMP / MTs by Mrs. Sri Harmanti, S.Pd from State MTs 3 Ponorogo. Currently the book is in the process of revision and maintenance of the ISBN.Keywords: modules, PPKN Teacher, teaching materialsABSTRAK Saat ini, guru-guru PPKn di MTs kabupaten Ponorogo membutuhkan informasi dan panduan agar mampu membuat modul sebagai bahan ajar. Modul tersebut berguna bagi kegiatan belajar mengajar di kelas.  Tujuan kegiatan ini agar guru-guru PPKn di MTs Kabupaten Ponorogo mampu: 1) Memahami materi tentang  modul, 2) Memahami tata cara penyusunan modul, dan 3) Menyusun/Membuat modul PPKn untuk SMP/MTs. kegiatan ini menggunakan metode pelatihan dan praktik dalam membuat modul, ceramah dan tanya jawab.  Dari 13 peserta menghasilkan modul PPKn untuk SMP/MTs kelas 7 dan 8. 12 peserta mampu menyelesaikan 1 bab modul, sedangkan 1 peserta lain mampu menyelesaikan 1 modul kelas 8 SMP/MTs oleh Ibu Sri Harmanti, S.Pd dari MTs Negeri 3 Ponorogo. Saat ini buku tersebut sedang proses revisi dan pengurusan ISBN. Kata kunci: bahan ajar modul, guru PPKn